Uma análise comparada das políticas de gestão docente nas Instituições de Ensino Superior privadas, na Bahia, com a burocracia profissional de Mintzberg - SANTIAGO, Nilzete Teixeira (2017)
The study analyzes factors that influence Bahia private HEI's Teacher Management Policies adherence to Mintzberg's Professional Bureaucracy Model, through the following specific objectives: Teacher Management Policies identification; comparison with Mintzberg's Professional Bureaucracy; adherence of these policies and practices to the Professional Bureaucracy. Mintzberg (2009) proposes 05 (five) types of organizational structures: Simple, Divided, Mechanistic Bureaucracy, Adhocracy and Professional Bureaucracy. In the last type, teachers are portrayed as autonomous professionals, performing their activities in a decentralized way, due to abilities considered for career progression. In order to achieve the study's goal, a quantitative, exploratory and descriptive approach was developed. A multiple cases study, in three (3) private HEI (a faculty, one university center and a university), in Bahia, was addressed, in order to guarantee an intentional sample's heterogeneity. Three (3) academic managers were interviewed, directly linked to the Teacher Management Process, knowledgeable about HEI's policies and practices. Results indicated that HEI Policies' level of adherence to Mintzberg's Professional Bureaucracy Model is associated with several factors, among them, academic organization type, number of teachers, HEI's legal nature, and association to educational groups. Such data analysis suggests a correlation between this model and capital-labor balancing forces.